The Influence of Surface Damage on Miniplates: A Study of Bacterial Attachment Across Various Strains [version 2; peer review: 1 approved, 2 approved with reservations] - Maria Goreti Widyastuti; Ahmad Kusumaatmaja; Tetiana Haniastuti; Bramasto Purbo Sejati (F1000Research)
Background Postoperative infection and rejection of miniplates in maxillofacial surgery are linked to surface irregularities and bacterial adhesion. This study investigated the physical and microbiological characteristics of patient-rejected miniplates to elucidate factors contributing to implant failure. Methods Forty miniplates, including straight-type BSSO and L-shaped designs, were collected from patients. Macro photography documented surface deformities. Contact angle measurements assessed surface wettability. Bacterial adhesion for Staphylococcus aureus, Streptococcus mutans, Pseudomonas aeruginosa, and Enterococcus faecalis was quantified via the crystal violet assay. Scanning electron microscopy (SEM) was used to visualize microbial colonization. Results Macro images showed visible deformations, especially in the bridge areas of straight-type BSSO plates. Contact angle analysis revealed significantly greater hydrophobicity in rejected plates than controls (mean: 89.6° vs. 72.3°, p < 0.01). Rejected plates demonstrated significantly increased adhesion of S. aureus and S. mutans (p < 0.001), particularly on mandibular plates. P. aeruginosa adhered more to control plates (p < 0.05), while E. faecalis showed no significant difference between groups. SEM confirmed dense bacterial clusters, with S. aureus forming cocci aggregates and S. mutans forming chains, particularly in regions of surface distortion. Conclusion Rejected miniplates exhibit increased surface roughness and hydrophobicity, correlating with elevated bacterial adhesion. These findings highlight the need for improved surface design or coating technologies to reduce biofilm formation and enhance clinical outcomes in maxillofacial surgery.